Experimental characterization of a small-scale solar Organic Rankine Cycle (ORC) based unit for domestic microcogeneration - Fatigati, Fabio; Vittorini, Diego; Di Bartolomeo, Marco; Cipollone, Roberto (Energy conversion and management, 2022)
[Display omitted] •Experimental assessment of an ORC plant bottomed to solar thermal flat collectors;•Analysis of ORC plant performances in steady and transient conditions;•Development of activation strategy of the ORC plant driven by the reservoir;•Evaluation of ORC performance considering domestic hot water demand variation;•Steady and transient analysis of the relation between ORC operating quantities; The integration of a Micro-Organic Rankine Cycle (ORC) power unit with conventional solar flat plate collectors ensures the simultaneous fulfillment of electricity and domestic hot water (DHW) demands. Due to the variability of the solar source, despite the introduction of a thermal storage unit, the plant is subject to severe off design operating conditions. A small-scale ORC-based was designed, built and fully tested, to experimentally assess the performance and operating robustness of the plant in steady and dynamic off-design condition. The unit is fed by hot water from a 135 L reservoir. Dedicated electric heaters (12 kW each one) reproduce the thermal availability from 15 m2 of standard solar thermal collectors for domestic applications. The test bench underwent an extensive experimental assessment in both stationary conditions of the hot source and in presence of a variable thermal load at the evaporator. Due to the plant architecture and components, the control of the unit is based on the variation of the mass flow rate of the working fluid (R245fa) matching the thermal equilibrium at the evaporator in each operating condition of the system. The variation of the flow rate, in fact, must fit with thermal power available. The off-design steady state assessment allows the understanding of the wide operability of the plant (17–62 g/s), with power and efficiency varying between 150 and 500 W and 2.4–4%, respectively. The dynamic testing of the pilot unit points out the plant consistency and robustness to severe off-design operation, mostly due to the 1 kW scroll expander, very suitable for time-varying operating conditions. Both the option of a full discharge of the thermal energy of the reservoir and the option of a split discharge to the evaporator were investigated and provided a clear indication on the CHP feasibility when no addition of thermal energy takes place at the reservoir. It was observed that during a complete reservoir thermal discharge, the plant works for 3000–3300 s continuously, with a slow power decrease from 500 W to 100 W. Considering the thermal energy recharging time, the plant could be averagely operated up to 7 times during the day if a partial discharge was performed. Each plant activation lasts 900 s producing a power ranging from 500 W to 200 W. This operating strategy allows to cover up to 11.2% of the whole electric energy yearly required by an average European household.